Complete conditioning for soccer - Alexander, Ryan P. (Champaign, Illinois Human Kinetics, 2021)
This book provides readers with a comprehensive overview on soccer conditioning for players of all levels. A heavy emphasis is placed on position specificity (e.g., conditioning for midfielders, conditioning for forwards, etc.) and injury prevention and management
Physical demands of soccer -- Fitness assessment and evaluation -- Conditioning for soccer -- Strength training -- Power development -- Speed and agility -- Match and training preparation -- Periodization and programming -- Recovery -- Injury prevention, injury management, and return to play
Includes bibliographical references and index
Keywords: Soccer -- Training